Meningkatkan Motivasi menjadi Mahasiswa yang berprestasi di masa Pandemi - Wita Hariani (Jurnal Abdimas Serawai, 2022)
Achievement motivation is the driving force to achieve the highest possible level of learning achievement for the sake of hope for himself. Achievement motivation is influenced by two internal and external factors. The higher the student achievement motivation, the better for student achievement gain academic at the time of this pademi. On the other hand, the lower the student's achievement motivation, the lower the academic achievement, especially during the pandemic. In this case, students with high achievement will succeed in understanding or obtaining high academic achievement and students with low achievement motivation on the contrary tend to obtain low academic achievement. There are four factors that determine the level of achievement motivation of a student, especially during the pandemic to carry out tasks, namely 1) the value placed on the success of the field (attainment or incentive value), 2) individual expectations of success, c) attribution of why someone succeeds or fails, d) Individual Formation standards. Meanwhile, someone who has high motivation has the characteristics of 1) having the desire to compete in a healthy manner with himself and with others, 2) having a better work desire, 3) thinking reality, knowing his abilities and weaknesses, 4) having responsibility. [personal, 5) Able to make breakthroughs in thinking, long-term strategic thinking, 6) always take advantage of feedback for improvement.